Genome-wide identification and evolution of the RCP gene family in soybean uncovers stress-responsive candidates - Xiaoli Guan; Run Yuan; Ao Shen; Yanhong Wang; Yuanmeng Yu; Liying Zou; Yuming Yang; Jinyu Zhang; Zhongwen Huang; Li Wang (Functional & Integrative Genomics, 2026)

Cross domain fault diagnosis of small modular reactor using sample synthesis and transfer learning with attention mechanism - Run Luo; Xiangcheng Pan; Yadong Li; Yang Liu; Hongtao Wan; Shun Hu; Tao Yu; Chao Xie (Annals of Nuclear Energy, 2026)

Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Bearing capacity envelopes of wide-shallow bucket foundations in sand under combined horizontal and moment loading - Run Liu; Rui Zhou; Xiang-chuan Meng; Yu Wang (Ocean Engineering, 2026)

Molecular adsorption and infrared-driven photocatalytic performance of nitrogen-defective g-C3N4 regulated by Ti doping and oxygen atmosphere treatment - Ziqian Zhang; Ziheng Li; Yu Wang; Yixuan Chen; Yitian Wang; Yuyang Guo; Run Liu; Guancheng Wang; Xingyu Gao; Youyu Pang (Journal of Environmental Chemical Engineering, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Investigating the therapeutic effects of injectable ammonium glycyrrhizate hydrogel co-loaded with doxorubicin and ATP in triple negative breast cancer - Wanying Chen; Xinyu Liu; Tiantian Guo; Keneng Cai; Wenli Cai; Run Xia; Mengyao Xu; Weichi Jiang; Chuyi Yu; Jianjia Feng; Chengli Ling; Sheng Zhou; et al. (Chemical Engineering Journal, 2026)

Dead pine tree detection using an iterative semi-supervised framework integrating expert annotation and active learning - Xiaolin Li; Run Yu; Yu Qiu; Jianlong Luo; Xiaojian Lu; Shiguo Huang; Songqing Wu; Feiping Zhang (Computers and Electronics in Agriculture, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Photoluminescent dual cross-linked ionogels with high-stretchability, multi-responsive, and self-adhesive properties for information encryption transmission and wearable sensors - Xinru Liu; Yu Wang; Jiaxin Tong; Qingshang Peng; Zhuoyou Gao; Jiali Zhang; Mingtao Run; Hongzan Song (Chemical Engineering Journal, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Climatic drying-wetting cycles induced dynamic coupling effect between 3D soil desiccation cracking and moisture redistribution - Yu-Xuan Chen; Jun-Zheng Zhang; Chao-Sheng Tang; Run-Yang Lan; Qing Cheng; Jin-jian Xu; Ben-Gang Tian (Journal of Hydrology, 2026)

Short-term transport of soluble ions from sludge-based biochar in soil under environmental stress: effects of placement mode - Zhichao Xu; RuRu Yu; Run Zhou; Guoren Xu (Journal of Environmental Management, 2026)

RDO3 REPRESSOR 27, a new MED25 allele, regulates seed dormancy dependent on DOG1 and ABA pathways in Arabidopsis - Yue Yang; Xiao-Ying Li; Run Ding; Hong Cao; Yongxiu Liu; Yu Li (Planta, 2026)

Biochemical and multi-omics analyses reveal skeletal muscle adaptation to chronic low-salinity stress of marine medaka (Oryzias melastigma) - Tian-Hong Chen; Qing-Hao Zhan; Xiao-Yu Zeng; Ning-Ning Ma; Qi-Liang Li; Run-Jie Jin; Jia-Lang Zheng; Qing-Ling Zhu (Fish Physiology and Biochemistry, 2026)

A subset of endogenous P2X5 transcripts encodes ATP-sensitive receptor isoforms - Xiao-Na Yang; Dong-Ping Wang; Chen-Hui Shen; Xi Chen; Ai-Xin Zhang; Meng Zhang; Xing Zhou; Yun Tian; Peng Cao; Michael X. Zhu; Hui Yang; Chang-Run Guo; et al. (Science Bulletin, 2026)

Undescribed and nephroprotective diterpenoids from Daphne genkwa - Hong-Bo Ye; Xian-Run Wu; Li Wang; Hui-Zhen Peng; Yu Duan; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Hirsutanines H−O, monoterpene indole alkaloids from Uncaria hirsuta with neuroprotective effects - Nan An; Lei-Ming Wu; Shu-Qi Wu; Jia-Luo Huang; Dong Huang; Fang-Yu Yuan; Yi-Ling Liao; Run-Zhu Fan; Xian-Yuan Yang; Gui-Hua Tang; Lu Gan; Sheng Yin (Phytochemistry, 2026)

The oldest rock in the Eurasian continent was reworked from Hadean protocrust - Xiao-Fei Qiu; Da Wang; Xi-Run Tong; Shi-Wen Xie; Nian-Wen Wu; Fei Liu; Yu-Sheng Wan (Gondwana Research, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

First isolation and identification of a rhabdovirus from bluegill sunfish (Lepomis macrochirus) - Haiyue Chen; Wangqian Xu; Dingzhe Zou; Baozhou Wu; Shuguang Hao; Huajia Yao; Jie Zhou; Ying Tian; Yifei Li; Run Yang; Yujie Gu; Yu Liu; et al. (Aquaculture, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

From species to therapeutic property: distribution differences of threatened Chinese medicinal plants under climate change - Yun-Han Chen; Rui Yang; Run-Han Jiang; Yu Xia; Ling-Feng Mao (Biodiversity and Conservation, 2026)

Correction to: CAS-ESM2.0 Dataset for the Carbon Dioxide Removal Model Intercomparison Project (CDRMIP) - Jiangbo Jin; Duoying Ji; Xiao Dong; Kece Fei; Run Guo; Juanxiong He; Yi Yu; Zhaoyang Chai; He Zhang; Dongling Zhang; Kangjun Chen; Qingcun Zeng (Advances in Atmospheric Sciences, 2026)

Tissue Tropism and Pathogenesis of LMBV in Largemouth Bass: A Comparative Study of Injection and Immersion Infection Models - Tianmei Hu; Dingzhe Zou; Baozhou Wu; Haiyue Chen; Shuguang Hao; Ying Tian; Wangqian Xu; Yifei Li; Jie Zhou; Run Yang; Jiping Zhang; Yu Liu; et al. (Journal of Fish Diseases, 2026)
Largemouth bass ranavirus (LMBV) poses a significant threat to the aquaculture industry by causing severe systemic disease and substantial economic losses. This study investigates the tissue distribution, pathological damage, and host response following LMBV‐GD1909 infection using two infection models: experimental injection and simulated natural immersion. In the injection model, infected fish exhibited clinical signs, including skin ulcers, haemorrhaging at fin bases, body darkening and organ swelling. Histopathological analysis revealed extensive multi‐organ damage, particularly in the liver, spleen, and kidney, characterised by necrosis, haemorrhage, vacuolar degeneration and inflammatory infiltration. Haematological and serum biochemical analyses indicated significant alterations in key parameters, including elevated WBC, RBC and GLU levels, and reduced PLT, TP and LDH levels, reflecting systemic physiological disruption. Viral dynamics analysis demonstrated the pantropic nature of LMBV, with rapid dissemination to multiple tissues post‐injection. The liver and spleen were identified as primary target organs, showing the highest viral loads and most severe pathology, indicating a direct correlation between viral load and organ dysfunction. In the immersion model, simulating natural infection, the gills and skin displayed the highest viral loads initially, identifying them as the major entry portals. The gills also served as a key site for viral replication, with a clear gradient of viral spread from external to internal tissues observed over time. This study comprehensively elucidates the tissue tropism, dissemination pathways, and pathological impact of LMBV, providing critical insights for developing targeted prevention and control strategies against LMBV.

Removal of hexavalent chromium from water using sulfidated nanoscale zero-valent iron: Regeneration and freeze–thaw stability, mechanism, and plant ecotoxicity - Wei Yuzhen; Cheng Aobo; Liu Bei; Ma Jushan; Muhammad Hamdan Rashid; Yu Jialu; Fasih Ullah Haider; Ma Shengyuan; Zhang Qinhu; Chu Run (Journal of Water Process Engineering, 2026)

Biochar–PGPR combination modulates physiology and rhizosphere microenvironment to improve drought resistance of Pinus massoniana seedlings - Hongyun Xu; Run Luo; Wei Zhou; Cun Yu (Plant and Soil, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Kerogen-driven synergistic interactions in oil shale and microplastics co-pyrolysis: mechanistic insights into product distribution and oil upgrading - Shuai Li; Erfeng Hu; Guangwen Xu; Jianglong Yu; Haifeng Gong; Zuohua Liu; Guocan Zheng; Run Dong; Fan Xu (Chemical Engineering Journal, 2026)

Investigating the failure mechanism of a landslide triggered by the combined effects of excavation and rainfalls through numerical approaches - Shu-wei Sun; Xin-yu Fu; Yuan Li; Qiang Wen; Run-jie Gong (Landslides, 2026)

Research on Intelligent Identification of Dike Hidden Hazards Based on GprMax Forward Modeling and YOLOv11 Deep Learning: A Case Study of Wenzaobang River in Shanghai - Fu-yu Jiang; Run Han; Li-kun Gao; Jiong Ni; Jun-kai Yu; Xiao-yu Xu (Applied Geophysics, 2026)

An Incorporating Pore Water Pressure Constitutive Model for Overconsolidated Clay and Calibration of Transient FE Parameters - Yu Jiang; Zewei Xu; Run Liu (Journal of Marine Science and Engineering, 2026)
The simulation accuracy of triaxial tests for oversolidated clay in transient finite element analysis is affected by soil constitutive model, permeability coefficient, overconsolidation ratio, shear rate and mesh size. This study introduces the concepts of overconsolidation parameters, potential strength, and hardening parameters from the unified hardening model into the modified Cam-Clay model. By integrating the generation mechanism of pore water pressure, a constitutive model for overconsolidated clay incorporating pore water pressure was developed, and its accuracy was validated through triaxial tests. By invoking the UMAT subroutine, accurate simulation of the undrained triaxial tests of overconsolidated clay was achieved in the static/general analysis in Abaqus. Based on this, model parameters for simulating triaxial tests of overconsolidated clay in transient analysis (Soils) were calibrated. The relationships between shear rate, mesh size, and soil parameters were quantified, providing a reference for similar engineering numerical simulations.

Simulation-to-Reality transfer learning with UAV-based imagery for forest inventory attribute prediction - Qing Guo; Linyuan Li; Run Yu; Zhuangzhuang Zhang; Huaguo Huang (Computers and Electronics in Agriculture, 2026)

Prediction on uplift displacement of tunnel induced by base grouting in soft clay - Jia-run Wu; Yu-liang Lin; Dan He; Ye Ma (Tunnelling and Underground Space Technology, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Unlocking the potential of high-entropy catalysts in selective electrocatalytic organic transformations - Meng Dan; Yu-Qi Zhang; Tao Wei; Run-Long Qi; Shishan Xue; Zhen Guo; Zhao-Qing Liu (Science Bulletin, 2026)

Pyrogenic carbon-stimulated nitrate-dependent anaerobic methane oxidation: insights into redox activity and conductivity in anaerobic methanotrophic archaea metabolism and microbial dynamics - Fangrui Cai; Yu Wang; Mengying Xie; Guanbin Li; Suicao Wang; Venea Dara Daygon; Dihua Tian; Gaofeng Ni; Xiang Liu; Run Zhang; Lirong Lei; Zhiguo Yuan; et al. (Water Research, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

miR-23a modulates chlorantraniliprole susceptibility by targeting SfGSTs3 in Spodoptera frugiperda (Smith) - Fan-Bin Kong; Yong-Po Lv; Bai-Zhong Zhang; Meng-Yuan Zhang; Ling-Ling Cui; Ren-Jie Li; Dong-Mei Chen; Yu-Yang Peng; Run-Qiang Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Dynamic oil fume exhaust method and calculation formula suitable for residential kitchens in cold regions - Kailiang Huang; Run Bai; Guohui Feng; Xiaoxu Li; Chaoying Fan; Helu Cao; Haipeng Yu (Building and Environment, 2026)

Analysis of odor and VOCs pollution in industrial parks of central inner Mongolia autonomous region based on mobile monitoring - Chaofei Li; Yuanhao Jia; Yu Qiu; Cheryl Marie Cordeiro; Sha Li; Yanying Chen; Jinxing Liu; Heinz W. Siesler; Hongkan Wu; Run Zhao (Atmospheric Environment, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Therapeutic Potential of Somatostatin and Its Analogues in Alzheimer’s Disease: From Molecular Mechanisms to Preclinical Studies - Kai Liu; Xi-Yu Zhang; Yan-Ting Wang; Run Wang; Run-Hao Jin; Yan-hua Bing (Molecular Neurobiology, 2026)

Identification of lncRNAs Associated with Imidacloprid Resistance in the Grain Aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) - Ling-Ling Cui; Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Jin-Song Zheng; Fan-Bin Kong; Run-Qiang Liu (Neotropical Entomology, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Scalable production of Actinidia arguta adventitious roots in air-lift bioreactors and their antibacterial efficacy against Staphylococcus aureus - Wen Jiang; Xue-Han Zong; Song-Hao An; Jing-Run Xiu; Shuo Yu; Ke-Xin Zhang; Yue-Jun Hao; Mei-Yu Jin (In Vitro Cellular & Developmental Biology - Plant, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

A correction method for unit internal skin friction of super-large diameter open-ended monopiles in clay - Zewei Xu; Chao Liang; Yu Jiang; Run Liu (Ocean Engineering, 2025)

Enzyme treatment combined with Maillard reaction modification of sunflower meal hydrolysates to prepare sunflower seed oil flavor enhancer - Shuai Xu; Qing Guo; Yu-Xuan Jin; Run-Yang Zhang; Hua-Min Liu; Zhao Qin; Xiu-Zhu Yu; Xue-De Wang (Food Chemistry, 2025)

Molecular docking screening of endogenous protease inhibitors in sea bass (Lates calcarifer) and in vitro validation of their inhibitory efficacy - Run-Jian Gao; Lu Sun; Sen-Di Zhou; Yu-Meng Liu; Wei-Qiang Qiu; Sheng-Ping Yang; Yun-Fang Qian (Food Bioscience, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Factors contributing to high oxidative stability in oil from long-term stored tiger nut (Cyperus esculentus L.): Endogenous components - Jia-Ke Li; Deng-Ju Cai; Hang-Yu Zhao; Yu-Xiang Ma; Xiao-Shuang Cai; Hua-Min Liu; Run-Yang Zhang (Journal of Stored Products Research, 2025)

Nitrogen Doped Glycerol-Based Biochar as Effective Catalyst Activating Peroxydisulfate for Organic Dyes Removal - Cai-Wu Luo; Chao Xie; Qing-Qing Chen; Yu Zhang; Liang Jiang; Run-Ze Zhao; Jing-Jing Luo; Tian-Jiao Jiang (Water, Air, & Soil Pollution, 2025)

Geochemistry characteristics and tectonic significance of the ‘ “mafic” S-type granites’ - Qiang Shi; Xiang-Zhi Chen; Run-Xiao Shu; Yu-Song Chen; Shi-Jie Wang; Zhong-Yuan Xu; Kai-Yun Chen; Guo-Chun Zhao (International Geology Review, 2025)

TSC2/mTORC1 integrates deoxynivalenol signals recognized by membrane receptors IR and EGFR to restrict intestinal stem cell function - Cai-xia Dou; Hao-zhan Qu; Ying-chao Qin; Xiao-fan Wang; Hui-chao Yan; Run-sheng Li; Yu-guang Zhao; Jia-yi Zhou; Xiu-qi Wang (Journal of Hazardous Materials, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Advancing phylogenomic marker design: Updated USCO and UCE databases of Collembola - Shiyu Du; Shengyang Zhang; Run Jiang; Daoyuan Yu; Nerivânia Nunes Godeiro; Feng Zhang (Zoologica Scripta, 2025)
Molecular markers are critical for elucidating the evolution and genetic diversity of species. The relentless progress and innovation in sequencing technology have enabled the acquisition of a vast repository of high‐quality organism genomic data. A more precise and high‐resolution set of molecular markers can provide deeper insights into species evolution. Collembola, as a key group of soil arthropods, has been the focus of extensive research due to its evolutionary and ecological importance. Recently, several chromosome‐level genomes of springtails have been sequenced. Our objective was to enhance molecular marker design to improve the accuracy and robustness of the Collembola database, focusing on universal single‐copy orthologues (USCOs) and ultraconserved elements (UCEs). We constructed a set of 4073 USCOs by examining 15 genomes, including 11 high‐quality genome data at the chromosome level. We then curated and adapted a customized BUSCO (Benchmarking Universal Single‐Copy Orthologues) dataset specifically designed for USCO evaluation. In addition, we developed a novel probe set for UCEs, comprising 67,707 baits targeting 2608 specific loci. We achieved the successful capture of 2089–3847 USCOs and 972–1405 UCEs across the 15 genomes under investigation. These markers were tested to assess their capture success and systematically validated against two previous phylogenomic studies. This approach is instrumental in species identification, phylogenomics, population genetics, and contributes significantly to advancing our understanding of evolutionary biology and ecology. Both datasets are freely available for download from figshare: https://doi.org/10.6084/m9.figshare.26839783 .

Study on the lateral breakout resistance of submarine pipelines in the sand wave area - Run Liu; Yinze Guan; Chengfeng Li; Xiang Sun; Yinuo Liu; Zheng Yu (Ocean Engineering, 2025)

Aptamer-modulated Pt/Au/MIL-100(Fe) nanozymatic activity for the colorimetric detection of deoxynivalenol in grains - Huang Dai; Junlan Yu; Run Zhou; Guijie Hao; Zhaohui Qiao; Zhe Feng; Xin Liu; Jie Bi; Jiahua Wang; Xiaodan Liu; Fuwei Pi; Yafang Shen (Food Chemistry, 2025)

The association between greenspace exposure and sperm quality: A retrospective cohort study focusing on sperm kinematics and the influence of buffer settings - Sixuan Zeng; Tingting Yang; Run Tian; Xin Jin; Lu Zhang; Fuping Li; Leyao Fu; Jiarui Cai; Junhao Liao; Guishuang Song; Xiaoli Luo; Yujue Wang; et al. (Environmental Research, 2025)

Physiological, transcriptomic and metabolomic responses of the marine diatom Phaeodactylum tricornutum to the auxin IAA - Yu-Ting Chen; Dong-Sheng Zhao; Xiao-Li Liu; Huan Yang; Run-Ze Gu; Nan Li; Xiufeng Yan; Hui-Xi Zou (Algal Research, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

An azacrown ether-based near-infrared fluorescent probe for the detection of Pb2+ and its applications in food, environmental water, plant and animal samples - Yueyuan Zhang; Huacong Wei; Yu Li; Zhuye Shang; Run Zhang; Zhiqiang Zhang; Qingtao Meng (Analytica Chimica Acta, 2025)

Improving the emulsification properties of corn starch by esterification combined with freeze-thawing and enzymatic treatment - Run Ji; Jieli Xu; Yuhe Yu; Shuang Song; Xiuling Zhang; Wentao Zhang (Food Chemistry, 2025)

Exploring the multifaceted roles of histone deacetylase inhibitor vorinostat in the cell growth, mycelial morphology, pigments, and citrinin biosynthesis of Monascus purpureus - Run-Ya Li; Chen-Yu Zhang; Shaoxiang Xiao; Xin-Yi Liu; Ru-Xue Li; Jing Li; Hao Li; Jun Liu (Archives of Microbiology, 2025)

Quantitative proteomics and integrated stress response analysis of the ccpA mutant of Lactococcus lactis N8 - Xian Xu; Wanjin Qiao; Yongping Xin; Yijiang Yu; Run Tian; Bolei Jiao; Haijin Xu; Mingqiang Qiao (Food Bioscience, 2025)

Highly stretchable, anti-freezing, self-adhesion and self-healing zwitterionic hydrogel electrolytes for flexible electronic devices - Jingxuan Zheng; Jingye Liang; Jishuai Xu; Fangying Lu; Hanbin Yu; Yong Liu; Run Wang (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Paleoproterozoic granite in the Khondalite Belt, northern margin of the North China Craton: Response to the assembly of the Columbia supercontinent - Qiang Shi; Run-Xiao Shu; Xiang-Zhi Chen; Guo-Chun Zhao; Yu-Song Chen; Zhao-Sheng Wang; Long Ma; Zhong-Yuan Xu; Zheng-Hong Liu; Kai-Yun Chen; Hui-Chu Wang (Precambrian Research, 2025)

Centrifuge model study of vertical ultimate bearing capacity of pile foundations in overconsolidated clay - Run Liu; Yu Jiang; Chengfeng Li; Guangsi Chen; Chunyang Su; Xiaoyu Long (Ocean Engineering, 2025)

Methane production related to microbiota in dairy cattle feces - Jian Liu; Meng Zhou; Lifeng Zhou; Run Dang; Leilei Xiao; Yang Tan; Meng Li; Jiafeng Yu; Peng Zhang; Marcela Hernández; Eric Lichtfouse (Environmental Research, 2025)

Integrated network pharmacology, bioinformatics, and experiment analysis to decipher the molecular mechanism of Salidroside on Gastric cancer via targeting NCOA4-mediated ferritinophagy - Yu Fu; Guiqin Huang; Yawen Cai; Menghui Ren; Run Cheng; Yuhui Chai; Yingdi Wang; Yunqi An; Tianhua Yan; Lingpeng Zhu; Xinxin Liu (Chemico-Biological Interactions, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Overexpression of CYP6CY1 is Involved in Imidacloprid Resistance in Sitobion miscanthi (Takahashi) (Homoptera: Aphidae) - Yun-Shan Xiong; Ling-Ling Cui; Gui-Lei Hu; Yu-Tai Jiang; Yong-Po Lv; Pei Zhang; Jin-Song Zheng; Bai-Zhong Zhang; Run-Qiang Liu (Neotropical Entomology, 2025)

Planar Hall plateau in magnetic Weyl semimetals - Lei Li; Chaoxi Cui; Run-Wu Zhang; Zhi-Ming Yu; Yugui Yao (Science Bulletin, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Evidence of polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs) in wild fish species from the remote tropical marine environment, south China sea - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zi-Ling Yu; Hai-Yang Shao; Bing-Zhong Yang; Zhong-Biao Chen; Bi-Xian Mai (Environmental Pollution, 2024)

Circ-Bptf Ameliorates Learning and Memory Impairments via the miR-138-5p/p62 Axis in APP/PS1 Mice - Hong-Fang Wang; Yi-Bo Li; Zi-Yu Liu; Wen-Meng Xie; Qing Liu; Run-Jiao Zhang; Wen-Yu Wang; Jia-Xin Hao; Lei Wang; Dan-Dan Geng (Molecular Neurobiology, 2024)

Exercise Alleviates Fluoride-Induced Learning and Memory Impairment in Mice: Role of miR-206-3p and PREG - Lei Chai; Qiqi Cao; Ke Liu; Run Zhu; Hao Li; Yanghuan Yu; Jixiang Wang; Ruiyan Niu; Ding Zhang; Bo Yang; Mohammad Mehdi Ommati; Zilong Sun (Biological Trace Element Research, 2024)

Dual-Functional group passivation to foster buried interface Cohesion for High-Performance perovskite photovoltaics - Namatullah Nizamani; Kai-Li Wang; Run-Jun Jin; Chun-Hao Chen; Jing Chen; Yu Xia; Lei Huang; Yu-Han Li; Mary Donnabelle Balela; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2024)

Antibacterial and antibiofilm efficacy of silver nanoparticles mediated by Oplopanax elatus adventitious root extract against mixed bacteria with different species - Ling-Hong Bai; Ming-Zhi Fan; Jing-Run Xiu; Ke-Xin Zhang; Zhong-Yu Zhou; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Genome-wide analysis of long non-coding RNAs involved in the fruit development process of Cucumis melo Baogua - Ya-hui Li; Chun Liu; Run-zhe Xu; Yu-peng Fan; Ji-yuan Wang; Hu Li; Jian Zhang; Hui-jun Zhang; Jing-jing Wang; Da-kui Li (Physiology and Molecular Biology of Plants, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

Study on the motion patterns of shallow-embedded pipelines in sand - Run Liu; Zheng Yu; Chengfeng Li; Xintong Hao (Marine Georesources & Geotechnology, 2024)

Numerical modelling of sand liquefaction via a weakly coupled approach between lattice spring and discrete element methods - Zhe Li; Gao-Feng Zhao; Yu-Jie Zhang; Zhi-Peng Hao; Kai-Li Niu; Run Liu (Computers and Geotechnics, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Developing a regional scale construction and demolition waste landfill landslide risk rapid assessment approach - Huanyu Wu; Qiaoqiao Yong; Jiayuan Wang; Weisheng Lu; Zhaoyang Qiu; Run Chen; Bo Yu (Waste Management, 2024)

Waste control by waste: Recovering iron from red mud with the effect of Phosphogypsum-included additive - Hong Yu; Long Liu; Mingxia Liu; Hanquan Zhang; Run Mao (Resources, Conservation and Recycling, 2024)

Ultra-long room temperature phosphorescent materials based on tetraphenylethylene derivatives for anti-counterfeiting and encryption applications - Jian-Hang Hu; Run-Xin Hou; Chun Liu; Yan-Ping Wang; Yu-Fei Liu; Ying Huang; Zhu Tao; Xin Xiao (Chemical Engineering Journal, 2024)

Two sex pheromone receptors for sexual communication in the American cockroach - Na Li; Renke Dong; Huanchao Zeng; Yan Zhang; Run Huang; Wei Liu; Fengming Cao; Jincong Yu; Mingtao Liao; Jingyou Chen; Wenlei Zhang; Zejian Huang; et al. (Science China Life Sciences, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Integrative Metabolomics and Whole Transcriptome Sequencing Reveal Role for TREM2 in Metabolism Homeostasis in Alzheimer’s Disease - Meng Wang; Tao Wei; Chaoji Yu; Ruiyang Li; Yunsi Yin; Hanchen Yang; Run Di; Xinyi Xia; Qi Qin; Yi Tang (Molecular Neurobiology, 2024)

MiRNA-seq and mRNA-seq revealed the mechanism of fluoride-induced cauda epididymal injury - Yanghuan Yu; Run Zhu; Mengjie Qi; Jie Liu; Kewei Cao; Ding Zhang; Bo Yang; Ruiyan Niu; Jundong Wang; Yangfei Zhao; Zilong Sun (Science of The Total Environment, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Seasonal predictability of SST anomalies and marine heatwaves over the Kuroshio extension region in the Copernicus C3S models - Chenguang Zhou; Hong-Li Ren; Yu Geng; Run Wang; Lin Wang (Ocean Modelling, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Reshaped buried interface by comprehensive passivation for highly efficient perovskite photovoltaics - Lei Huang; Kai-Li Wang; Run-Jun Jin; Jing Chen; Chun-Hao Chen; Yu Xia; Yan-Hui Lou; Zhao-Kui Wang (Chemical Engineering Journal, 2024)

CAS-ESM2.0 Dataset for the Carbon Dioxide Removal Model Intercomparison Project (CDRMIP) - Jiangbo Jin; Duoying Ji; Xiao Dong; Kece Fei; Run Guo; Juanxiong He; Yi Yu; Zhaoyang Chai; He Zhang; Dongling Zhang; Kangjun Chen; Qingcun Zeng (Advances in Atmospheric Sciences, 2024)
Understanding the response of the Earth system to varying concentrations of carbon dioxide (CO 2 ) is critical for projecting possible future climate change and for providing insight into mitigation and adaptation strategies in the near future. In this study, we generate a dataset by conducting an experiment involving carbon dioxide removal (CDR)—a potential way to suppress global warming—using the Chinese Academy of Sciences Earth System Model version 2.0 (CAS-ESM2.0). A preliminary evaluation is provided. The model is integrated from 200–340 years as a 1% yr −1 CO 2 concentration increase experiment, and then to ~478 years as a carbon dioxide removal experiment until CO 2 returns to its original value. Finally, another 80 years is integrated in which CO 2 is kept constant. Changes in the 2-m temperature, precipitation, sea surface temperature, ocean temperature, Atlantic meridional overturning circulation (AMOC), and sea surface height are all analyzed. In the ramp-up period, the global mean 2-m temperature and precipitation both increase while the AMOC weakens. Values of all the above variables change in the opposite direction in the ramp-down period, with a delayed peak relative to the CO 2 peak. After CO 2 returns to its original value, the global mean 2-m temperature is still ~1 K higher than in the original state, and precipitation is ~0.07 mm d −1 higher. At the end of the simulation, there is a ~0.5°C increase in ocean temperature and a 1 Sv weakening of the AMOC. Our model simulation produces similar results to those of comparable experiments previously reported in the literature.

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

A DEM-based approach for modeling the thermal-mechanical behavior of frozen soil - Ruohan Sun; Run Liu; Huan Zhang; Rui Zhang; Yu Jiang; Ruilong Yin (European Journal of Environmental and Civil Engineering, 2024)

Study on indoor thermal perception, behavioral adaptation in late pregnancy and their effects on adverse birth outcomes in south China - Jie Ni; Huailin Wang; Xinyue Yu; Run Gao; Yanqiu Li; Zhaosong Fang; Jason Kai Wei Lee; Zhenghong Zhu; Maimaitiminjiang Wulayin; Xin Chen; Cunrui Huang; Qiong Wang (Building and Environment, 2024)

Recent developments on the removal of zinc from electric arc furnace dust by using microwave heating - Yuandong Xiong; Kai Wang; Dejin Qiu; Mamdouh Omran; Run Huang; Ying Li; Shiyu Wei; Inam Ullah Khan; Dengwei Zhang; Abdallah Ahmed; Yaowei Yu (Environmental Science and Pollution Research, 2024)

Physicochemical properties of clayey deposits slurry treated by lime-activated ISSA and GGBS considering seawater salinity effect - Zhao Sun; Wen-Bo Chen; Run-Dong Zhao; Jiang-Shan Li; Zhen-Yu Yin; Jian-Hua Yin; Yong-Gui Chen (Applied Clay Science, 2024)

Outdoor artificial light at night and male sperm quality: A retrospective cohort study in China - Run Tian; Tingting Yang; Chenghan Xiao; Fuping Li; Leyao Fu; Lu Zhang; Jiarui Cai; Sixuan Zeng; Junhao Liao; Guishuang Song; Chuan Yu; Ben Zhang; et al. (Environmental Pollution, 2024)

Automatic identification of illegal construction and demolition waste landfills: A computer vision approach - Qiaoqiao Yong; Huanyu Wu; Jiayuan Wang; Run Chen; Bo Yu; Jian Zuo; Linwei Du (Waste Management, 2023)

Study on the dynamic embedment variation of shallow embedded submarine pipelines in sand - Zheng Yu; Run Liu; Chengfeng Li; Xintong Hao (Ocean Engineering, 2023)

The role of the gut-liver axis in modulating non-alcoholic fatty liver disease through dietary patterns and microecological agents - Yucheng Fang; Ziyang Fang; Ziwei Li; Run Yu; Haimeng Zhang; Qinwen Wang; Xiangrong Cheng; Guowei Le; Guoqing Wu (Food Bioscience, 2023)

Theoretical and Numerical Studies on the Coupling Deformation of Global Lateral Buckling and Walking of Submarine Pipeline - Run Liu; Xintong Hao; Chengfeng Li; Qingxin Li; Zheng Yu; Dang Zhao (Journal of Ocean University of China, 2023)

Biomethane is produced by acetate cleavage, not direct interspecies electron transfer: genome-centric view and carbon isotope - Jian Liu; Jiafeng Yu; Yang Tan; Run Dang; Meng Zhou; Marcela Hernández; Eric Lichtfouse; Leilei Xiao (Bioresource Technology, 2023)

Ozone catalytic oxidation of toluene over triple perovskite-type catalysts modified with KMnO4 - Hsin Tzu Chuang; Run Yu Liu; Minh Man Trinh; Moo Been Chang (Environmental Science and Pollution Research, 2023)

Identification, quantitative and bioactivity analyses of aroma and alcohol-soluble components in flowers of Gardenia jasminoides and its variety during different drying processes - Run Yu; Yue Li; Dun Si; Shulei Yan; Jingjing Liu; Jinping Si; Xinfeng Zhang (Food Chemistry, 2023)

Composites of TiO2 pillared sericite: Synthesis, characterization and photocatalytic degradation of methyl orange - Yu Liang; Wei Li; Baohui Bei; Chong Li; Zetian He; Xuan Wang; Run Zhou; Hao Ding; Shu Li (Applied Clay Science, 2023)

Micro-mechanism insights into the adsorption of anionic dyes using quaternary ammonium-functionalised chitosan aerogels - Nan Du; Li-Yuan Huang; Yan-Shu Xiong; Run Tian; Jiang-Yu Yin; Dan-Yu Cao; Dong-Bin Hu; Hai-Qin Lu; Wen Li; Kai Li (Carbohydrate Polymers, 2023)

Nano-Fe promotes accumulation of phytoestrogens and volatile compounds in Trifolium pratense flowers - Yitong Li; Run Li; Xiaoyan Ren; Tian Wang; Haitao Yu; Quan Liu (Theoretical and Experimental Plant Physiology, 2023)

Antimicrobial resistome during the transition from an integrated to a monoculture aquaculture farm in southern China - Jin-Tao Yang; Dan-Yu Xiao; Li-Juan Zhang; Hai-Xin Chen; Xing-Run Zheng; Xiao-Li Xu; Hong-Xia Jiang (Science of The Total Environment, 2023)

Projected change of East-Asian winter precipitation related to strong El Niño under the future emission scenarios - Yu Huang; Hong-Li Ren; Jong-Seong Kug; Run Wang; Jingxin Li (Climatic Change, 2023)

Trehalose prevents glyphosate-induced hepatic steatosis in roosters by activating the Nrf2 pathway and inhibiting NLRP3 inflammasome activation - Cai-Yu Lian; Run-Zhou Wang; Jie Wang; Zhen-Yong Wang; Wei Zhang; Lin Wang (Veterinary Research Communications, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Variations in the concentration, source and flux of polycyclic aromatic hydrocarbons in sediments of the Pearl River Estuary: Implications for anthropogenic impacts - Yali Li; Nairong Guo; Ke Yuan; Baowei Chen; Junjie Wang; Maofeng Hua; Jing Yu; Jingyan Hu; Run Lu; Shichun Zou; Ying Yang (Science of The Total Environment, 2023)

Reducing light exposure enhances the circadian rhythm of the biological clock through interactions with the gut microbiota - Yu Zhang; Yong Li; Yilin Yuan; Jun Wang; Shiyu Zhang; Run Zhu; Yan Wang; Yinbao Wu; Xindi Liao; Jiandui Mi (Science of The Total Environment, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

Three-dimensional agricultural water scarcity assessment based on water footprint: A study from a humid agricultural area in China - Yunan Yan; Run Wang; Si Chen; Yu Zhang; Qianli Sun (Science of The Total Environment, 2023)

Hierarchical porous nanosilica derived from coal gasification fly ash with excellent CO2 adsorption performance - Yanfang Liu; Zhiqiang Wang; Wenhui Zhao; Jili Hou; Longpeng Cui; Liang Zou; Chenghao Li; Hongwei Li; Yu Wu; Run Xu; Yongfa Zhu (Chemical Engineering Journal, 2023)

Study on salt expansion mechanism of subgrade-culvert transition section in saline soils and cold regions - Yu Zhang; Run-ze Tian; Tian-liang Wang (Cold Regions Science and Technology, 2023)

Effects of the probability of pulse-like ground motions on landslide susceptibility assessment in near-fault areas - Jing Liu; Hai-ying Fu; Ying-bin Zhang; Pei-yi Xu; Run-dan Hao; Hai-hong Yu; Yun-yong He; Hong-yan Deng; Lu Zheng (Journal of Mountain Science, 2023)

Ozone catalytic oxidation of low-concentration formaldehyde over ternary Mn-Ce-Ni oxide catalysts modified with FeOx - Run Yu Liu; Minh Man Trinh; Hsin Tzu Chuang; Moo Been Chang (Environmental Science and Pollution Research, 2022)

Robiginitalea marina sp. nov., isolated from coastal sediment - Xiao-Qi Xuan; Run-Yuan Mao; Wen-Xing Yu; Jing An; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Effect of enhanced UV-B radiation on growth and photosynthetic physiology of Iris tectorum maxim - Run Chu; Qin-hu Zhang; Yu-zhen Wei (Photosynthesis Research, 2022)

Trophinin-associated protein expression correlates with shorter survival of patients with glioma: a study based on multiple data fusion analysis - Yong Sun; Zhen Dong Liu; Run Ze Liu; Xiao Yu Lian; Xing Bo Cheng; Yu Long Jia; Bin Feng Liu; Yan Zheng Gao; Xinjun Wang (Molecular Biology Reports, 2022)

Screening and production of dsRNA molecules for protecting Cucumis sativus against Cucumber mosaic virus through foliar application - Qin Mo; Beibei Lv; Yu Sun; Xiao Wu; Lili Song; Run Cai; Xueming Tang (Plant Biotechnology Reports, 2022)

Gastrodin Attenuates Lipopolysaccharide-Induced Inflammatory Response and Migration via the Notch-1 Signaling Pathway in Activated Microglia - Yue-yi Yao; Run Li; Yan-ji Guo; Yu Zhao; Jia-zhi Guo; Qing-long Ai; Lian-mei Zhong; Di Lu (NeuroMolecular Medicine, 2022)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Cyclic response of monopile-supported offshore wind turbines under wind and wave loading in sand - Rui Liang; Yu Yuan; Dengfeng Fu; Run Liu (Marine Georesources & Geotechnology, 2021)

CsUFO is involved in the formation of flowers and tendrils in cucumber - Yue Chen; Haifan Wen; Jian Pan; Hui Du; Keyan Zhang; Leyu Zhang; Yao Yu; Huanle He; Run Cai; Junsong Pan; Gang Wang (Theoretical and Applied Genetics, 2021)

Genome-Wide Identification and Expression Analysis of Heavy Metal Stress–Responsive Metallothionein Family Genes in Nicotiana tabacum - Qin Yu; Linshen He; Chunsong Huo; Xiaohan Jiang; Hua Chen; Run Wang; Minzhi Tang; Ling Dong; Ji Chen; Yonghao Li; Shunqin Zhu; Wanhong Liu (Plant Molecular Biology Reporter, 2021)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

Synaptic Adaptation Contributes to Stimulus-Specific Adaptation in the Thalamic Reticular Nucleus - Yu-Ying Zhai; Ryszard Auksztulewicz; Pei-Run Song; Zhi-Hai Sun; Yu-Mei Gong; Xin-Yu Du; Jie He; Xiongjie Yu (Neuroscience Bulletin, 2020)

Deformation and failure of a high-steep slope induced by multi-layer coal mining - Jian-le Yu; Jian-jun Zhao; Hao-yuan Yan; Qi-yi Lai; Run-qiu Huang; Xiu-wei Liu; Yang-chnn Li (Journal of Mountain Science, 2020)

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Effect of Interaction between Adenosine and Nitric Oxide on Central Nervous System Oxygen Toxicity - Cheng-wei Xie; Zhong-zhuang Wang; Ya-nan Zhang; Yu-liang Chen; Run-ping Li; Jun-dong Zhang (Neurotoxicity Research, 2019)

Analysis of genetic variation of porcine circovirus type 2 within pig populations in central China - Peng-Li Xu; Yu Zhao; Hui-Hua Zheng; Run-Bo Tian; Hao-Ying Han; Hong-Ying Chen; Lan-Lan Zheng (Archives of Virology, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Evaluation of the possible slip surface of a highly heterogeneous rock slope using dynamic reduction method - Guo-qing Chen; Run-qiu Huang; Feng-shou Zhang; Zhen-fei Zhu; Yu-chuan Shi; Jian-chao Wang (Journal of Mountain Science, 2018)

Centrifuge model test of an irrigation-induced loess landslide in the Heifangtai loess platform, Northwest China - Sheng-hua Cui; Xiang-jun Pei; Hao-yu Wu; Run-qiu Huang (Journal of Mountain Science, 2018)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Efficient yeast cell-surface display of an endoglucanase of Aspergillus flavus and functional characterization of the whole-cell enzyme - Gang Gao; Run-Qian Mao; Yue Xiao; Jing Zhou; Yu-Huan Liu; Gang Li (World Journal of Microbiology and Biotechnology, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

Identification and characterization of multiple porcine astrovirus genotypes in Hunan province, China - Chao-Ting Xiao; Zhang Luo; Sun-Liang Lv; Tanja Opriessnig; Run-Cheng Li; Xing-Long Yu (Archives of Virology, 2017)

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

XCI-escaping gene KDM5C contributes to ovarian development via downregulating miR-320a - Yi-Xi Sun; Yi-Xin Zhang; Dan Zhang; Chen-Ming Xu; Song-Chang Chen; Jun-Yu Zhang; Ye-Chun Ruan; Feng Chen; Run-Ju Zhang; Ye-Qing Qian; Yi-Feng Liu; Lu-Yang Jin; et al. (Human Genetics, 2017)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

The influence of nitrogen on the development and accumulation of protein bodies in the developing endosperm of wheat caryopses - Fei Xiong; Xu-Run Yu; Liang Zhou; Jing Zhang; Bo Li; Jian Liu; Feng Wang; Ai-Sheng Xiong (Molecular Biology Reports, 2014)

Structural development of aleurone and its function in common wheat - Fei Xiong; Xu-Run Yu; Liang Zhou; Zhong Wang; Feng Wang; Ai-Sheng Xiong (Molecular Biology Reports, 2013)

Design and Synthesis of a Ruthenium(II) Complex-Based Luminescent Probe for Highly Selective and Sensitive Luminescence Detection of Nitric Oxide - Xiaojing Yu; Run Zhang; Zhiqiang Ye; Bo Song; Jingli Yuan (Journal of Fluorescence, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Effect of Different Levels of Copper and Molybdenum Supplements on Serum Lipid Profiles and Antioxidant Status in Cashmere Goats - Wei Zhang; Yu Zhang; Shi W. Zhang; Xian Z. Song; Zhi H. Jia; Run L. Wang (Biological Trace Element Research, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

A minimum traveltime ray tracing global algorithm on a triangular net for propagating plane waves - Shi-Jian Yu; Run-Ze Liu; Jiu-Long Cheng (Applied Geophysics, 2010)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)

A new method for protein domain recognition - Zhen-Yu Xuan; Lun-Jiang Ling; Run-Sheng Chen (European Biophysics Journal, 2000)